Water as an environmentally friendly propellant for a multi-functional spacecraft architecture - Tejeda,J; Schwertheim,A; Knoll,A (International Journal of Energetic Materials and Chemical Propulsion, 2023)
Water can be utilized as spacecraft propellant to dramatically reduce the environmental impact of constructing and operating a satellite. In this work, a multi-mode chemical-electrical propulsion system, in which water was used as the propellant in both high thrust chemical and high specific impulse electrical maneuvres, was studied. This type of system allows the spacecraft architecture community to divest from traditional propellants such as hydrazine and xenon, thus reducing the production of highly toxic chemicals and dramatically reducing the carbon footprint of propulsion systems. Water has the lowest toxicity, carbon footprint, and price of any current or proposed propellant, and has been shown in laboratory testing to be a feasible alternative compared to traditionally used propellants. The unique role it can play across multiple spacecraft subsystems suggests that the commercial adoption of water as a propellant will reduce cost and mass while also reducing the environmental impact of the satellites of tomorrow. This technology has the ability to enable the development of modular, multifunctional, competitive, and environmentally friendly spacecraft architectures.